Building a hair: tip growth in Arabidopsis thaliana root hairs. - Carol, R; Dolan, L (2002)
The Arabidopsis thaliana root hair is used as a model for studying tip growth in plants. We review recent advances, made using physiological and genetic approaches, which give rise to different, yet compatible, current views of the establishment and maintenance of tip growth in epidermal cells. For example, an active calcium influx channel localized at the tip of Arabidopsis root hairs has been identified by patch-clamp measurements. Actin has been visualized in vivo in Arabidopsis root hairs by using a green-fluorescent-protein-talin reporter and shown to form a dense mesh in the apex of the growing tip. The kojak gene, which encodes a protein similar to the catalytic subunit of cellulose synthase, is needed in the first stages of hair growth. A role for LRX1, a leucine-rich repeat extensin, in determining the morphology of the cell wall of root hairs has been established using reverse genetics. The new information can be integrated into a general and more advanced view of how these specialized plant cells grow.